Energy Efficient Solar Fruit Dryer (Czech Journal of Multidisciplinary Innovations, 2022)
this article shows the design of the experimental sample, the load capacity of raw materials is 50 kg, air heaters with a total area of 7 m2 for solar dryers were carried out supporting experimental work for agricultural products. During the experiment, the results showed that time (26 hours) apples were dried to 15% moisture, pears showed a result of 25%, and control samples-42-45%. Temperatures were determined, the results were achieved when heating the air in the dryer from the sun at a power of 2 kWh, that is, 1300 m3/h. In the course of the experiment, these results became known that the disadvantages and descriptions of the designed solar dryer were described in detail.